Subjective trust model for mobile ad-hoc network in emergency environment - Abu Bakar A.; Ismail R.; Ahmad A.R.; Abdul Manan J.-L. (2023)
Trust is a directional relationship between two parties; the trustor and trustee. To manage trust, a procedure for trust management is needed. Trust in Mobile Ad-Hoc Network (MANET) during emergency case involves probability since it is not absolutely certain how much the nodes can be trusted, because there is not enough information collected by the time the decision needs to be made, hence creates uncertain environment. This paper focuses on the use of subjective logic in creating a trust model for evaluating nodes' trustworthiness at the emergency site. Nodes need to share information during emergency cases, hence before access is granted, nodes must be proven authentic. A trust model that consists of two important components which are trust formation and trust calculation is then proposed and verified. 2012 IEEE.